The Pengembangan Aplikasi Mikroorganisme Lokal (MOL) pada Produksi Padi (Oryza sativa L.) di Kecamatan Jiwan, Madiun - Ratih Kemala Dewi; Rika Candra Nur Aini (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Excessive use of inorganic fertilizers has led to land degradation. There need efforts to increase land fertility to increase rice production. One way that can be done is utilizing local microorganisms (MOL) to improve the soil quality. Therefore, productivity can be increased. Community development activities were aimed to socialize the use of MOL in increasing rice production. Community development activities were carried out on January 20-April 20, 2020, at the Dadi Rukun farmer group association (Gapoktan), Sukolilo Village, Jiwan District, Madiun, East Java. The method used is to make a demonstration plot (demplot) of rice production using MOL in the residents' rice fields about 3000 m2. The demplot was given with three kinds of treatment, they were organic fertilizer 200 kg ha-1 with MOL application, 50% an-organic fertilizer (75 kg ha-1 NPK dan 75 kg ha-1 urea) with MOL application, and 100% an-organic fertilizer (150 kg ha-1 NPK dan 150 kg ha-1 urea) without MOL application. Each treatment was repeated 3 times. Apart from using the demplot, socialization activities were also carried out by holding meetings between farmers and field extension workers, practitioners from academia and students who carry out fieldwork practices (PKL) in the village. Feedback in the form of farmer responses is given before and after the end of the activity as evaluation material for the success of the program. The experimental results showed that there was no significant difference in the rice production variables in the three treatments. MOL can be used as an alternative to liquid organic fertilizer to support rice production. Community empowerment activities carried out greatly affect changes in knowledge, perspectives, and skills of farmers in making and utilizing MOL to support rice production so that assistance efforts must continue to be improved.